An Examination of Cybercrimes Leading to Vulnerabilities in Energy, Transportation, and Financial Systems - Ni Ketut Tri Srilaksmi; Moh. Erkamim; Naylah Dzakiah; Ngakan Kompiang Adi Suardana; Ni Kadek Sri Devi Putri Swambini (Catuspata, 2023)
The commencement of the current decade is the primary milestone in the progression from Industry 4.0 to Society 5.0. The contemporary period necessitates the ability of individuals from all strata of society to effectively acclimate to the rapid advancements in technology. In the context of Society 5.0, which emphasizes the central role of human beings in generating novel value through technical advancements, there exists the potential to mitigate future disparities among individuals and address economic challenges. The potential risks that may emerge are diverse, intangible in tangible terms, and characterized by uncertainty. The aforementioned threat is a cyber threat that possesses the capacity to inflict significant losses upon a nation. One potential future development of significant consequence involves the occurrence of cyberattacks against essential national assets or critical infrastructure, including but not limited to renewable energy facilities, transportation networks, and financial institutions. Hence, it is imperative for all nations to possess the capability to effectively organize training programs, establish fresh military units, and enhance their individual national defense capabilities. In brief, the text elucidates the prevailing societal transition towards Society 5.0, which underscores the vital role of humans in technology progress. This highlights the potential advantages of this transition, such as the mitigation of inequalities and economic difficulties, while also stressing the importance of implementing strong cybersecurity protocols to prevent possible cyber risks in this dynamic technological environment.